2020
DOI: 10.1002/ajcp.12483
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Hashtag: Online Disclosure of Mental Illness and Community Response on Tumblr

Abstract: People with mental illness may disclose information on social media to build social capital.• Mental health disclosures included themes of emotions, interpersonal loss, and change.• Disclosure frequency increased with community responses in interaction with diagnosis.• Community responses varied as a function of mental health diagnosis disclosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…For instance, Hawkins and Haimson [ 31 ] pointed out that Tumblr may create novel opportunities for trans people to combat widespread violence and stigmatization, possibly enhancing positive mental health benefits in three ways: (1) as a therapeutic outlet to discuss emotions throughout the transition process; (2) as a place to observe others’ transition-related content; and (3) as a way to interact with and positively impact others. Such a finding is consistent with Griffith and Stein [ 10 ]. In addition to confirming that posting content on Tumblr is often considered therapeutic on its own accord (regardless of interactions with others), these authors showed that Tumblr communities could be quite active in supporting their members’ mental health disclosures.…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…For instance, Hawkins and Haimson [ 31 ] pointed out that Tumblr may create novel opportunities for trans people to combat widespread violence and stigmatization, possibly enhancing positive mental health benefits in three ways: (1) as a therapeutic outlet to discuss emotions throughout the transition process; (2) as a place to observe others’ transition-related content; and (3) as a way to interact with and positively impact others. Such a finding is consistent with Griffith and Stein [ 10 ]. In addition to confirming that posting content on Tumblr is often considered therapeutic on its own accord (regardless of interactions with others), these authors showed that Tumblr communities could be quite active in supporting their members’ mental health disclosures.…”
Section: Introductionsupporting
confidence: 93%
“…This bias seems particularly relevant, considering that previous contributions highlighted that the characteristics and affordances of a medium are not background elements, but can define in unexpected ways how it will be used and which users will find it suitable for their intentions [ 7 , 8 , 9 ]. According to Griffith and Stein [ 10 ], each SNS has its own reputation based on branding and self-selected user communities, meaning that the same person could tend to select different SNSs for different uses. That could explain why 98% of users who are active on a social platform are also active at least on one other SNS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations